Estimating vertical foreclosure in US gasoline supply - Zava Aydemir; Stefan Buehler (University of Zurich, Socioeconomic Institute, 2002)
We examine the competitive effects of the vertical integration of gasoline refineries and retailers in the U.S. Adapting the first-order condition approach of static oligopoly games to the analysis of vertically related oligopolies, we develop a novel framework for directly evaluating the strategic foreclosure effect and the effciency benefits associated with vertical integration. Applying this framework, we find significant evidence for both vertical foreclosure and effciency benefits. The foreclosure effect dominates the effciency benefits for more than half of the refining firms in the sample. Vertical foreclosure is found to increase the wholesale price of refined gasoline by 0.2 to 0.6 cents per gallon.
Keywords: L13; L22; L49; L71; 330; vertical integration; separation; foreclosure; market conduct; petroleum industry; Vertikale Konzentration; Erdölraffinerie; Benzin; Theorie; USA